(untitled) (translation. a transdisciplinary journal, 2022)
Translating is sometimes analogized to a bridge-building undertaking in which linguistic and cultural disparities among communities are, as it were, reconnected in the post-Babel dispersal of human tongues. Translation creates connectedness, undoubtedly, yet as Michael Cronin has pointed out, "connectedness has as a necessary prerequisite the identification and maintenance of separateness"